The mature larva of Heinrichiella obscura (Gravenhorst) and a review of the larval morphology of Ophioninae [Hymentoptera: Ichneumonidae] - Wahl, David B.; Shaw, Mark R. (Zootaxa, 2025)
The mature larva of the western Palaearctic ichneumonid Heinrichiella obscura (Gravenhorst) is described for the first time and the morphology is placed in the context of the genus being a basal lineage of the Ophioninae. The described larvae of Ophioninae are reviewed and a new larval diagnosis of the family is provided.